Existence and Effectiveness of Sharia Tourism at the Sheikh Zayed Grand Mosque Solo - Ajis Subhan Edi; Muthoifin (al-Afkar, Journal For Islamic Studies, 2024)
The existence of Sharia tourism is considered to have provided many significant benefits for various groups who use it because they see the characteristics of a place and services. The provision of products and services offered by tourist places, objects and destinations in halal tourism is not much different from products, services, objects and destinations in general tourism. This research is a descriptive study using qualitative analysis. Data collection in this study was carried out by observing, interviewing and documenting. The results of this study indicate that the Sheikh Zayed Solo Grand Mosque is not yet effective for Sharia tourism and is still far from being called Sharia Tourism because the Sheikh Zayed Solo Grand Mosque sees the absence of several supporting factors such as Halal/Halal culinary food and drinks, accommodation factors such as sharia hospitality. around the mosque, the travel agency factor that has not been provided, and the absence of tour guides who work according to the Sharia Tourism SOP.